2018
DOI: 10.1155/2018/5809656
|View full text |Cite|
|
Sign up to set email alerts
|

A Rare Anatomical Variation of the Termination of Right and Left Cephalic Veins

Abstract: Clinically, the cephalic vein is preferred for haemodialysis in patients with chronic renal failure (CRF), to remove waste products from blood. The cut-down of cephalic vein in the deltopectoral groove is preferred when superior vena caval infusion is necessary. However, cephalic veins exhibit a wide array of developmental variations in terms of formation, course, and termination. In this report, we describe a case of an anomalous cephalic vein with a bifid course of terminations on both left and right upper l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
1
0
2
Order By: Relevance
“…Based on the classification, Kameda et al [13] suggested each frequency of subtypes as 0.4%, 1.2%, 0.4%, and 0.2%, respectively. They suggested single case report related with the variations [1,5,14,15,21,23,25,33,35] and we found some more case reports related with this variation: three for subtype 1A [2,8,12], three for subtype 1B [19,27], and one for subtype 2A [9]. The case 1 and 2 belong to subtype 1B and 1A, respectively.…”
Section: Discussionsupporting
confidence: 55%
“…Based on the classification, Kameda et al [13] suggested each frequency of subtypes as 0.4%, 1.2%, 0.4%, and 0.2%, respectively. They suggested single case report related with the variations [1,5,14,15,21,23,25,33,35] and we found some more case reports related with this variation: three for subtype 1A [2,8,12], three for subtype 1B [19,27], and one for subtype 2A [9]. The case 1 and 2 belong to subtype 1B and 1A, respectively.…”
Section: Discussionsupporting
confidence: 55%
“…De acuerdo a los estudios consultados, la terminación en forma simple es la conformación más frecuente, hecho concordante con nuestros resultados. Sin embargo, numerosos autores han señalado la existencia de terminaciones dobles del AVC, al igual que las encontradas en el presente estudio (Kian & Asif, 2008;Daoui & Asif;Russo et al, 2017;Maalman et al, 2018).…”
Section: Discussionunclassified
“…Esta variación tiene una frecuencia del 0,7 % al 5,4 % en la bibliografía consultada. Corresponde al remanente embriológico denominado vena yugulocefálica persistente (VYC), típica de primates no humanos, y reportada de manera esporádica en humanos (Jun et al, 2017;Latarjet & Ruiz Liard;Maalman et al;Novakov & Krasteva;Russo et al) Así mismo, la literatura describe casos en los que el AVC puede drenar también en la vena yugular interna (VYI) o directamente en la vena subclavia (VS), siendo esta última, la variación más frecuente (Kiev & Asif; Lau et al).…”
Section: Discussionunclassified
“…In the article titled “A Rare Anatomical Variation of the Termination of Right and Left Cephalic Veins” [ 1 ], there were errors in the Abstract and the Introduction section.…”
mentioning
confidence: 99%